2011
DOI: 10.1007/s10773-011-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

The Inevitability of Fine Tuning in a Complex Universe

Abstract: Why should the universe need to be fine tuned? The thesis is presented that parameter sensitivity arises as a natural consequence of the mathematics of dynamical systems with complex outcomes. Hence, fine tuning is a mathematical correlate of complexity and should not elicit surprise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This indeed has been one of the conclusions in [7] as summarized more elegantly in [12]; as well as [10] where, reviewing the alternative universe landscapes studied by [7,12,[15][16][17] it has been observed that if one is prepared to adjust another parameter in a compensating manner, it might be possible to find other regions in the parameter space that are also congenial. However, that does not remove the fine-tuning problem, as the alternative values are still finely tuned and this is inevitable to produce complexity as observed in our present universe.…”
Section: Case Iii: Left Half Of the Trianglementioning
confidence: 82%
See 1 more Smart Citation
“…This indeed has been one of the conclusions in [7] as summarized more elegantly in [12]; as well as [10] where, reviewing the alternative universe landscapes studied by [7,12,[15][16][17] it has been observed that if one is prepared to adjust another parameter in a compensating manner, it might be possible to find other regions in the parameter space that are also congenial. However, that does not remove the fine-tuning problem, as the alternative values are still finely tuned and this is inevitable to produce complexity as observed in our present universe.…”
Section: Case Iii: Left Half Of the Trianglementioning
confidence: 82%
“…It is increasingly being understood that if there is complexity, fine-tuning is inevitable [10]. Even if one is not happy with anthropic arguments, we simply cannot get away from fine-tuning.…”
mentioning
confidence: 99%
“…Furthermore, maybe there is a deep link between the different constants and physical laws, such that it makes no sense to change just one parameter at a time. Changing a parameter would automatically perturb other parameters (see [11], p1581). Fortunately, more recent research have gone much further than these one-parameter variations.…”
Section: Gregory Chaitin ([12] P339)mentioning
confidence: 99%
“…Stenger (2011) and Bradford (2011 attempt to play down the accuracies claimed of fine-tuning, whilst Aguirre (2001) casts doubt on its limited scope.…”
mentioning
confidence: 99%